Mengungkap Dimensi Pemaknaan Hunian - Hutomo, Cahyo S.; Kusuma, Hanson E. (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2021)
Urbanization is increasing the need for and building sites and vertical housing. Changes in residential typology cause changes in housing preferences and meanings. This study aims to reveal the dimensions of residential meanings — the study conducted in two stages with a sequential mix-method. The first stage is qualitative research using an explorative grounded theory approach. The categories and variables identified in the first stage of the research are used in the second phase of research quantitatively using the correlational research approach. The data collected were analyzed by factor analysis to reveal the dimensions of residential meaning — the dimensions of the revealed mapping distinguished by the type of occupancy, namely site, and vertical dwelling. The vertical house tends to be perceived as having more social and physiological significance, personalization, tranquility, hiding, economy, and self-actualization than site occupancy.